Five-year clinical and radiographic outcomes using pedicle screw only constructs in the treatment of adolescent idiopathic scoliosis - Hwang, Steven W. (Springer-Verlag, 2012)
PURPOSE: To determine the mid-term clinical and radiographic impact of pedicle screw fixation in patients with adolescent idiopathic scoliosis (AIS). METHODS: A multicenter AIS database was retrospectively queried to identify 99 consecutive patients who underwent posterior spinal fusion using an all pedicle screw construct with a minimum of 5-year follow-up. Radiographic and clinical parameters were reviewed at regular intervals up to 5 years. RESULTS: The mean age was 14.4 ± 2.0 years with 79 % being female. The mean preoperative major curve was 51.7 ± 14.2° with a mean correction of 66 and 64 % at 2 and 5 years (p = 0.16). Pre-op thoracic kyphosis averaged 22.3 ± 12.9° and was 18.4 ± 10.6° at 5 years with no significant change from 2 years (p = 0.33). SRS total and domain scores demonstrated significant improvements at 2 years, which were slightly decreased at 5 years (p = 0.06). SRS scores of self-image (p = 0.99) and satisfaction (p = 0.18) were significantly improved after surgery with minimal change by 5 years. The change in SRS total scores from 2 to 5 years was attributed to differences in SRS scores of pain and mental health (p < 0.05). CONCLUSIONS: Intermediate follow-up of patients with AIS treated with an all pedicle screw construct demonstrates maintenance of their coronal, and sagittal plane correction between 2- and 5-year follow-up. At 5 years, improvements in SRS scores were consistent with 2-year values, except for a decline in pain and mental health scores.